A computational study on the cyclic softening and fatigue behaviour of medical PEEK. Issue 1 (17th December 2018) - Beckmann, Agnes; Ma, Songyun; Zhang, Le; Stoffel, Marcus; Markert, Bernd
Abstract: In the underlying study, a computational method to predict the cyclic plastic deformation and the fatigue life of medical PEEK is proposed. The OHNO‐WANG plasticity model was implemented as an Abaqus® user subroutine. The SMITH‐WATSON‐TOPPER criterion was implemented as a postprocessing Python script to predict the fatigue failure of PEEK. The validation of the OHNO‐WANG model with the five effective cyclic stable stress‐strain hysteresis curves show a very good agreement. The fatigue model was calibrated with a good final goodness of fit.